PERAN TEKNOLOGI PENDIDIKAN TERHADAP PERUBAHAN PEMBELAJARAN PENDIDIKAN JASMANI - Akbar Syafruddin (FKIP Palangka Raya University, 2023)
This study aims to determine how the role of educational technology to changes in physical education learning. To answer the problems in this study, it was carried out using the literature study method. Literature study is a series of activities related to methods of collecting library data, reading and taking notes, and managing research materials. The literature search process in this article uses Google Scholar by utilizing various national and international research results published between 2013 and 2023 with the keywords education technology and physical education. These articles are then used as a basis for answering the problems in this research. The conclusion in this study is that physical education must be developed in ways such as: developing the abilities of physical education teachers, developing teaching materials, and creating an assessment system in the learning process by utilizing advances in technology and information. This is very important in order to produce quality teachers and human resources who are competent and competitive in accordance with the progress of the times. Keywords : Educational Technology, Learning, Physical Education